Perceived trends in viewing the future by Croatian and Slovenian business students : implications for managerial education - Peterlin, Judita (Array, 2019)
This paper presents appreciative inquiry (AI) methodology in the context of management education. Therefore, we propose that AI, which focuses on positive aspects of doing business, needs to be implemented into management education of future managers in Slovenia and Croatia and we provide empirical evidence of thinking patterns of business students studying at the University of Ljubljana and the University of Split. For comparison, we investigated the previous experiences and future expectations of business students in Croatia and Slovenia. Empirical part is composed of two parts: qualitatively based AI and a quantitative study, based on statistical methods. Results show a positive outlook of business students in both countries.